Strategy for Instilling Religious Values ​​in the Formation of Early Childhood Morals at Birrul Walidain Takeran Magetan Preschool - Rulik Endarwati (LP3M STAI MA'ARIF MAGETAN, 2023)
Early childhood education aims to facilitate holistic growth and development of children from all aspects of a child's personality. The purpose of this study is to determine the implementation of the cultivation of religious values in the formation of early childhood morals and to determine the inhibiting factors for the cultivation of religious values in PAUD Birrul Walidain Takeran Magetan. The method used in this study is to use field research with a learning strategy approach. As a result, the storytelling method makes it easy for early childhood to understand and understand what is being taught by educators. In addition, educators can instill religious values in children by introducing them to early childhood, by telling the stories of the apostles, teaching religious values in everyday life through example. The inhibiting factors come from students and from the school, such as the level of intelligence of educators and teaching methods, as well as family background.